Optimasi Sistem Regenerasi dan Transformasi Padi Varietas Elit Indonesia - Aniversari Apriana; Toto Hadiarto; Ahmad Dadang (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2013)
New ricevariety can be generated by means of transgenic approach.Transgenic rice researches have been conducted in manyinstitutions worldwide using Japonica, Indica, and Javanicavarieties. The most cultivated rice in Indonesia is Indica.Indica type is known to have low responsive tissues inculture and transformation media when compared toJaponica rice. This research activity is aimed to optimizeregeneration and transformation systems of the Indonesianelite rice varieties, so that good method can be achieved tobe used in the generation of transgenic elite rice varieties ofIndica type. The research consisted of two activities:regeneration and transformation optimizations in varieties ofDodokan (upland rice) and Inpari 6 (irrigated rice).Immature embryo was used as the explant in this research.The optimization studies used 2 types of media, NBH (N6salts and vitamins, cassamino acid 0.5 g/l, L-proline 0.5 g/l,sucrose 20 g/l, D-glucose 10 g/l, 2.4-D 2 mg/l, NAA 1 mg/l, BA1 mg/l, agarose Type I 5.5 g/l) and NBH-M (N6 macro salts,B5 micro salts, and vitamins, 0.3 g/l cassamino acid, 3 g/l Lproline,20 g/l sucrose, 3 mg/l 2.4-D, 1 mg/l NAA, 1 mg/l BAP,5.5 agarose Type I), 2 types of regeneration media, R1 (MSbase media and vitamis, 0.3 g/l glutamine, 30 g/l sucrose, 2mg/l kinetin, 1 mg/l NAA, 3 g/l phytagel) and R2 (MS basemedia and vitamins, 2 g/l cassamino acid, 20 g/l sucrose, 30mg/l sorbitol, 2.5 mg/l kinetin, 0.25 mg/l NAA, 3 g/l phytagel).Optimization transformation of Indonesian elite rice varietiesused developed an empty plasmid pCAMBIA 1301 containinghpt gene. The transformation was conducted using twotypes of co-cultivation media, K1 (N6 macro salts, B5 microsalts, and vitamins, 0.5 g/l cassamino acid, 0.5 g/l L-proline,20 g/l sucrose, 10 g/l glucose, 2 mg/l 2.4-D, 1 mg/l NAA, 1mg/l BAP, 0.1 mM acetosyringone) and K2 (N6 macro salts,B5 micro salts, and vitamins, 0.5 g/l cassamino acid, 0.5 g/l Lproline,20 g/l sucrose, 10 g/l glucose, 2 mg/l 2.4-D, 1 mg/lNAA, 1 mg/l BAP, 0.2 mM acetosyringone). The resultsshowed that Inpari 6 could form embryonic calli in NBHmedia and further regenerated well in R1 media (13.8%).The co-cultivation media K1 generated more selected calliwhich then generated green plant of young embryocompared to K2. Inpari 6 showed higher regeneration ratesafter transformation (3.6%) compared to Dodokan (0%).Molecular analysis showed that all 11 transformants (Inpari6) tested contained the hpt gene. These results are expectedto support the development of transgenic Indica ricegeneration in Indonesia.